EPR spectroscopy identifies Met and Lys residues that are essential for the interaction between the CusB N-terminal domain and metallochaperone CusF. Issue 7 (8th July 2015) - Meir, Aviv; Natan, Adi; Moskovitz, Yoni; Ruthstein, Sharon
<x xml:space="preserve">Abstract</x> Methionine and lysine residues are important for preserving the structure of the CusB N-terminal domain and for the interaction with CusF.